Application of Heuristic Algorithm in Medical Informatics System for Patient Data Management in Southeast Asia - Setyani, Seswiyati Asri; Mahendro Prasetyo Kusumo (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
This research aims to analyze the application of heuristic algorithms in medical informatics systems for managing patient data in Southeast Asia. This research method uses qualitative research. This research data uses secondary data. Data includes scientific literature, technical reports, policy documents, and statistical data from trusted sources such as reputable journals, conferences, books, and health institutional reports. Data analysis using Nvivo 12 Plus software to identify relevant patterns and themes. This research indicates that Southeast Asian countries have begun to adopt information technology in health services. The implementation of the Electronic Medical Record (EMR) System has been used in several large hospitals in Malaysia and Thailand to integrate patient data digitally. The most prominent theme in the data findings regarding the role of heuristic algorithms in managing patient data is the importance of data security, management, optimization, efficiency, and blockchain integration in patient health services. Plus, the challenges heuristic algorithms face in healthcare include infrastructure, data fragmentation, cross-platform system integration, data security and privacy, big data analysis (big data), and potential heuristic algorithms. The significant impact is improving the efficiency, quality, and accessibility of health services. One of the main impacts is increasing operational efficiency. The implications of this research recommend that policymakers and health institutions adopt heuristic algorithms in medical informatics systems for managing patient data in hospitals to improve the quality of health services